1974
DOI: 10.1159/000180366
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Permeability to Protein Molecules – its Possible Structural Basis

Abstract: The ultrastructural basis of glomerular permeability to protein molecules is reviewed. These studies have relied either on the intrinsic electron density of intravenously injected tracer molecules, or on the peroxidatic activity of a number of peroxidatic enzymes of varying molecular weight. The nature of the final filtration barrier in the glomerulus remains conjectural but two possibilities have been suggested: the glomerular basement membrane (a) is the sole filter and retards the passage of protein molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

1974
1974
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…Previous studies (4,5,(12)(13)(14)(15)(16) demonstrate that both structures may be important for maintaining a stringent barrier for plasma proteins larger than 70 kDa. This study provides compelling evidence of the GESD and nephrin as the primary regulators of glomerular vascular permeability.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies (4,5,(12)(13)(14)(15)(16) demonstrate that both structures may be important for maintaining a stringent barrier for plasma proteins larger than 70 kDa. This study provides compelling evidence of the GESD and nephrin as the primary regulators of glomerular vascular permeability.…”
Section: Discussionmentioning
confidence: 97%
“…Tracer experiments with ferritin have suggested that the fenestrated endothelium with a potential pore size of 500 -1000-Å diameter is freely permeable to many large plasma proteins (3)(4)(5)(6)(7)(8)(9)(10)(11). Such studies have also implicated that the crucial barrier for plasma proteins larger than 70 kDa is maintained by the glomerular basement membrane (GBM) 1 and the glomerular epithelial slit diaphragms (GESD) (4,5,(12)(13)(14)(15)(16). The question as to which of these two substructures is important for normal glomerular permselectivity remains open.…”
mentioning
confidence: 99%
“…This knowledge has been based largely on experiments using tracers which can be visualized at the ultrastructural level (28,29). The early studies of Farquhar et al (6), showed that the lamina densa of the GBM behaved as a filtration barrier for large protein molecules, such as ferrifin; later studies using peroxidatic enzymes of mol wt ranging from 12,000-240,000 indicated that a second filtration barrier resides in the slit pore complex (7,9,10,28).…”
Section: Current Concepts Of Normal Glomerular Filtrationmentioning
confidence: 99%
“…Recent studies of the glomerular capillary wall suggest an additional barrier to the passage of plasma proteins, at least to those of molecular size of albumin and larger. This barrier appears to be at the slit pore between the foot processes of the visceral epithelial cells [14,28,32].…”
mentioning
confidence: 99%